ANALYSIS OF TRANSLATION PROBLEMS OF SCIENTIFIC DEGREES IN UZBEK AND ENGLISH LANGUAGES - Mamadaliyeva Moxizarxon Tursinali qizi (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
In translating academic (scientific) degrees from one language into another, a number of problems arise that not every translator is able to solve. The fact is that there are only three of them in the English-speaking countries system of academic degrees. Philosophy does not mean philosophy itself, but the whole complex of disciplines in a broad sense. Therefore, this degree is also held by specialists in the field of technical, economic, legal, medical, chemical, philological, mathematical and philosophical sciences.